Body Image, Quality of Life, and Their Predicting Factors in Pregnant Women: A Cross-Sectional Study - Rezaei Fard, Zeynab; Azadi, Arman; Veisani, Yousef (Kesmas, 2022)
Pregnancy can influence women’s psychological health, including body image and quality of life. This study aimed to examine the relationship between body image and quality of life and their predicting factors in pregnant women. This cross-sectional study was conducted on 250 pregnant women referred to health centers in Ilam City, Iran. Participants were selected using a random sampling method. Data collection tools comprised a sociodemographic questionnaire, Body Image Concern Inventory (BICI), and quality of life questionnaire (Short Form-12). Data were analyzed using statistical software. The mean ± SD of body image concern and quality of life was estimated at 31.77 ± 9.86 and 54.62 ± 15.71, respectively. There was a significant and negative correlation between body image and quality of life (p-value = 0.001, r = -0.313). Also, the most important predictors of body image were vitality, body mass index (BMI), general health, and unintended pregnancy, respectively, and body dissatisfaction was the most significant predictor of quality of life. This study revealed some variables affecting pregnant women’s body image and quality of life. Further studies are required to consider other factors influencing body image and quality of life among pregnant women.